Tin-mediated phase-controlled growth of γ-InSe thin films on Si (100) via molecular beam epitaxy - Abdelmajid Salhi (9178041) (2025)
Indium selenide is a III-VI semiconductor with promising electronic and optoelectronic properties, but its polymorphism makes single phase growth difficult, hindering its use in advanced electronic and photonic devices. In this study, we introduce a novel phase-selective growth of γ-InSe using tin (Sn)-mediated Molecular Beam Epitaxy (MBE) on Si (100). By tuning Sn flux during indium and selenium co-evaporation, we demonstrate a phase transition from γ-In2Se3 to γ-InSe. X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) confirm the absence of Sn within the grown films, indicating that Sn irradiation facilitates the displacement of Se adatoms from the surface, effectively lowering the effective Se/In flux ratio. This reduction favors the formation of γ-InSe over γ-In2Se3 as confirmed by Raman spectroscopy, mimicking the effect of reduced Se supply. Density functional theory calculations showed that SnSe clusters have lower formation energies than InSe clusters, indicating that Sn preferentially binds with Se. Furthermore, SnSe clusters exhibit weaker adsorption on the Si (100) surface compared to InSe clusters, suggesting that SnSe desorbs more readily. These findings offer new insights into surfactant-mediated phase engineering and pave the way for the scalable integration of single-phase γ-InSe on silicon for future electronic and optoelectronic applications. Other Information Published in: Applied Surface Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apsusc.2025.164367